Literasi Pertanian dan Pengaruhnya Terhadap Produktivitas Hasil Panen di Indonesia - Nacing, Nursyawal Nursyawal; Ismaya, Ismaya; Mustakim, Mustakim; Elihami, Elihami (Maktabatun: Jurnal Perpustakaan dan Informasi, 2023)
Abstract: The study conducted at Universitas Muhammadiyah Enrekang in January 2023 used content analysis to analyze data from various literature sources. The research aimed to understand the role of literacy in enhancing the productivity of farmers, as it contributes to more effective and sustainable farming practices. Factors influencing literacy include formal education, access to information and training, membership in the farmer's group or organization, and farmer's experience. Social-economic factors such as poverty, unemployment, and lack of education also affect literacy levels. The study found that farmers with better literacy levels have better agricultural productivity. This is due to better access to information, better training, and better knowledge of modern farming practices. Additionally, farmers with better literacy levels are more likely to adopt modern farming technologies, such as modern irrigation systems, greenhouses, and greenhouse technology. To improve literacy levels in farmers, measures such as providing more information and training, developing relevant non-formal education programs, and fostering collaboration between government, research institutions, and farmer organizations are needed.